Effect of tracheal suction on oxygenation, circulation, and lung mechanics in newborn infants. Issue 5 (May 1981) - Simbruner, G; Coradello, H; Fodor, M; Havelec, L; Lubec, G; Pollak, A
Abstract : Transcutaneous PO2, heart rate, and aortic blood pressure were measured i 10 mechanically-ventilated newborn infants to assess the degree and course of hypoxaemia, and to monitor the cardiovascular and respiratory changes during tracheal toilet. Five infants weighed less than 1250 (mean 994), g and 5 infants weighed greater than 1750 (mean 2216) g. During tracheal suction the TcPO2 fell from 68 +/- 27 (mean +/- SD) to 43 +/- 23 mmHg, and the heart rate from 144 +/- 8 to 123 +/- 25 beats/minute, but the blood pressure increased from 44 to +/- 24 to 49 +/- 24 mmHg. Hypoxaemia (TcPO2 less than 50 mmHg) occurred in 7 of 8 initially well-oxygenated infants when suctioned. The decrease in TcPO2 was similar for both groups of infants. It was greater in infants with controlled ventilation and an F1O2 greater than or equal to 0.8 than in infants with intermittent mandatory ventilation and an F1O2 less than 0.8. The TcPO2 fall correlated well with the TcPO2 during the control period but not during the time that the infants were disconnected from the respirator. A critical re-evaluation of routine tracheal toilet is needed.